In vitro interactions between lactic acid solution and art glass-ionomer cements - Linda Wang; Daniela Francisca Gigo Cefaly; Janaína Lima dos Santos; Jean Rodrigo dos Santos; José Roberto Pereira Lauris; Rafael Francisco Lia Mondelli; Maria Teresa Atta (University of São Paulo, 2009)
OBJECTIVES: Production of acids such as lactic acid contributes to establish a cariogenic environment that leads to dental substrate demineralization. Fluoride plays an important role in this case and, as fluoride-releasing materials, glass-ionomer cements are expected to contribute to minimize deleterious reactions. This study evaluated interactions of glass-ionomer cements used in atraumatic restorative treatment (ART-GICs) with an aqueous lactic acid solution, testing the null hypotheses that no changes occur in the pH of the solution or on the surface roughness and mass of the ART-GICs when exposed to lactic acid solution over a 6-week period. MATERIAL AND METHODS: Ketac Molar, Fuji IX, Vitro Molar and Magic Glass were tested, and compared to Filtek Z250 and Ketac Fil Plus as control groups. Six specimens of each material were made according to manufacturers' instructions. The pH of the solution and roughness and mass changes of each specimen were determined over 6 weeks. Each specimen was individually stored in 2 mL of 0.02 M lactic acid solution for 1 week, renewing the solution every week. pH of solution and mass of the specimens were monitored weekly, and surface roughness of the specimens was assessed before and at the end of the 6-week acid challenge. pH and mass data were analyzed statistically by repeated measures using one-way ANOVA and Tukey's post-hoc tests for each material. Paired t-tests were used for roughness analysis. Tukey's post-hoc tests were applied to verify differences of final roughness among the materials. Significance level was set at 5%. RESULTS: The null hypotheses were partially rejected. All materials were able to increase the pH of the lactic acid solution and presented rougher surfaces after immersion, while mass change was minimal and generally not statistically significant. CONCLUSIONS: These findings can be helpful to predict the performance of these materials under clinical conditions. A protective action against the carious process with significant surface damage due to erosion may be expected.